2022
DOI: 10.1002/ecs2.4215
|View full text |Cite
|
Sign up to set email alerts
|

Mammal responses to predator scents across multiple study areas

Abstract: Antipredator behaviors allow prey to mitigate the impacts of their predators. We investigated antipredator responses of two herbivore species, roe deer and European hare, and one mesopredator, red fox, toward predation risk imposed by lynx and wolf. We collected data (using camera traps) on visitation frequency and vigilance behavior to olfactory predator stimuli during 158 standardized scent trials in five areas across Europe, where lynx and wolves either occurred or had been absent for centuries. After a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…The absence of any response to wolf urine may also be a result of predator hunting strategies. Cursorial predators might fail to evoke strong anti‐predatory responses in deer, as opposed to pronounced effects as observed in the case of cues from ambush predators (Preisser et al., 2007 ; Sunde et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of any response to wolf urine may also be a result of predator hunting strategies. Cursorial predators might fail to evoke strong anti‐predatory responses in deer, as opposed to pronounced effects as observed in the case of cues from ambush predators (Preisser et al., 2007 ; Sunde et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…As large carnivores, with special reference to wolves, are quickly increasing in Europe and their number is far from being stabilized, their impact on their prey may therefore become greater in the next decades and can potentially change predator–prey relationships. Besides these density‐mediated impacts on ungulate prey species, several studies have demonstrated the importance of the behaviourally mediated effects on ungulate prey species and mesocarnivores induced by the presence and patterns of space use of large carnivores, which also occur in human‐dominated landscapes of Europe (Bubnicki et al., 2019; Diserens et al., 2021; Kuijper et al., 2014; Sunde et al., 2022; van Beeck Calkoen et al., 2021; Wikenros et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Besides these density-mediated impacts on ungulate prey species, several studies have demonstrated the importance of the behaviourally mediated effects on ungulate prey species and mesocarnivores induced by the presence and patterns of space use of large carnivores, which also occur in human-dominated landscapes of Europe (Bubnicki et al, 2019;Diserens et al, 2021;Kuijper et al, 2014;Sunde et al, 2022;van Beeck Calkoen et al, 2021;Wikenros et al, 2017).…”
Section: Management Implicationsmentioning
confidence: 99%
“…The absence of any response to wolf urine may also be a result of predator hunting strategies. Cursorial predators might fail to evoke strong anti-predatory responses in deer, as opposed to pronounced effects as observed in the case of cues from ambush predators [52,53].…”
Section: Discussionmentioning
confidence: 99%